BUILDING A SCALE OF COMPETENCE TO APPLY INTERDISCIPLINARY INTEGRATED KNOWLEDGE INTO PRACTICE FOR STUDENT: Received: 04th November 2022; Revised: 02nd January 2023, 13th January 2023, 28th January 2023; Accepted: 03rd February 2023 - Thi Kiem Thu, Tran (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Vietnam began to implement a new general education program to replace the previous one in 2018. According to the new program, the content has many topics that integrate interdisciplinarity. Therefore, teachers need to be able to teach in the direction of interdisciplinary integration to develop students’ competence. The current situation in Vietnam shows that teachers are still not confident because they do not have much interdisciplinary integrated knowledge in applying integrated knowledge into practice to the teaching process. This leads to the consequence that when they teach topics related to real life, it will not be feasible, reducing the effectiveness of teaching in schools, and difficult to achieve the goals required by the Ministry of Education and Training. For the above reasons, universities that train pedagogical students also need to make appropriate adjustments to foster and train pedagogical students’ competence in applying interdisciplinary knowledge into practice. The article presents the research results on the process of building and designing the scale, which are specific criteria to measure and evaluate the competence to apply knowledge in the practice of physics pedagogical students. In addition, we also propose an illustrative example to contribute to improving the quality of training for students of Physics pedagogy.